Analisis Kesiapan Laboratorium Kultur Jaringan Tingkat SMK dalam Pembelajaran dan Kewirausahaan - Dumaris Taruli Artha Siahaan; Bebi Ramalia Alfi; Ixora Sartika Mercuriani; Rahmania Pamungkas (Postgraduate, University of Mataram, 2026)
This research evaluates the readiness of the tissue culture laboratory at SMK Negeri 1 Pandak using an observation instrument of laboratory preparedness. This study focused on the laboratory infrasturucture and management system as the primary object of observation in seven aspects. The instrument's validation was conducted by two Expert of Tissue Culture experts to yield Aiken's V validity coefficients for the seven aspects of laboratory readiness observation instrument ranging from 0.585 to 0.661, indicating that the instrument is valid. Observations of the tissue culture laboratory's readiness also revealed an average total readiness percentage of 76.72%, with the infrastructure (84.61%), facilities (85.84%), and administration (85.71%) aspects categorized as